Una Yupana dinámica para cada niño. (2004)
In this article, it describes the calculator Dynamic Yupana, based on the ancient Incas abacus, From the beginning,  this calculator has been created for children, It is in fact a game, appropriated to acquire mental ability, to increase concentration  capacity and to obtain selfconfidence. The usefulness focused on the basic operation and on the square root, makes part of the  good application. But the field keeps open to new discoveries and new work sources.